Current trends and prospects for the development of food production in the regions of Kazakhstan - Abraliyev, O.; Baimbetova, A.; Kusmoldayeva, Zh.; Korostyshevskaya, E. (Journal of Economic Research & Business Administration, 2025)
In developed countries, supporting agricultural producers is considered a key goal of government policy. Support for the agricultural industry is focused on subsidies, modernizing production technologies, purchasing fertilizers, increasing the competitiveness of agricultural products, supporting industry research through regulatory and methodological support, and implementing tax, budgetary, and customs tariff measures. The research purpose was to analyze the significance of potato cultivation by examining key metrics such as cultivation area, total yield, productivity, and fertilizer usage. It utilized methods like descriptive statistics, quartile analysis, and regression analysis to derive insights from the available data. Originality/value of the research lies in its comprehensive evaluation of how potato production impacts Kazakhstan’s food security. By providing detailed statistics, such as Pavlodar region’s cultivation area of 24,033.5 hectares and its yield of 6,616,240.6 centners, the study offers a nuanced understanding of the sector’s contribution to the national food supply. Findings reveal that potato production is crucial for Kazakhstan’s food security. Regions like Pavlodar and Ulytau, with high yields and productivity levels (e.g., 293.6 centners per hectare in Ulytau region), underscore the efficiency of potato farming. The study also highlights the role of effective fertilizer management in enhancing productivity,vital for maintaining a stable food supply and ensuring nutritional security. Key words: potato production efficiency, agriculture of Kazakhstan, food security, economic regions of Kazakhstan.